Experimental validation of energyPlus simulation of a single storey building. - Baharun, A. (Universiti Malaysia Sarawak, (UNIMAS), 2011)
EnergyPlus simulated indoor temperature of a single storey building at the east campus of Universiti Malaysia Sarawak, for April and June, are validated with measurements taken in 2007.